Effect of estimating gestational age by ultrasound cephalometry on the specificity of alpha-fetoprotein screening for open neural-tube defects. - Wald, N; Cuckle, H; Boreham, J; Turnbull, A (1982)
A total of 1268 women had a maternal serum alpha-fetoprotein (AFP) screening test for open neural-tube defects between 15 and 22 weeks gestation and a routine ultrasound examination at their first antenatal visit. All had a singleton infant without a neural-tube defect. AFP values were expressed as multiples of the normal median at the relevant gestational age (MoM). The percentage of women with raised maternal serum AFP levels was less when gestation was estimated by the fetal biparietal diameter (BPD) than when the time since the first day of the last menstrual period (LMP) was used; 1.8% compared with 2.3% at a serum AFP cut-off level of 2.5 MoM. Different ultrasound policies were compared for their effect on AFP screening and the best was found to be routine BPD measurement used together with a higher cut-off level than usual. For example, using a cut-off level of 3.0 MoM the detection rate for open spina bifida at 16-18 weeks gestation would be about 88% and the proportion of unaffected singleton pregnancies with raised levels only 0.9%. These results are materially better than those achieved by a policy of scanning only those women with a raised AFP level (79% and 1.4% respectively with a more conventional cut-off level of 2.5 MoM) or, in addition, scanning those with doubtful gestational ages (82% and 1.7% respectively with a cut-off level of 2.5 MoM).